ISOLATION AND IDENTIFICATION OF PHYTOSTEROLS FROM BIGNONIA VENUSTA (L.) - Sharma, Manoj; Khichar, Mukesh Kumar; Rd, Agrawal (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To isolate phytosterols from Bignonia venusta (L.) and its antimicrobial activity. Introduction: B. venusta is an important medicinal plant known for its vast potential. It is a valuable plant which is commonly used in traditional system of medicine for relieving pain and inflammation, as well as in a number of metabolic disorders such as diabetes and obesity. Methods: In the present study, phytosterols from B. venusta was identified and quantified in vivo. Phytosterols were identified using chromatographic and spectral studies. Conclusion: B. venusta (L.) is an ideal source of phytosterols and act as antimicrobial agent.Â 